Trajectories of childhood immune development and respiratory health relevant to asthma and allergy - Tang,HHF; Teo,SM; Belgrave,DCM; Evans,MD; Jackson,DJ; Brozynska,M; Kusel,MMH; Johnston,SL; Gern,JE; Lemanske,RF; Simpson,A; Custovic,A; et al. (eLife, 2018)
Events in early life contribute to subsequent risk of asthma; however, the causes andtrajectories of childhood wheeze are heterogeneous and do not always result in asthma. Similarly,not all atopic individuals develop wheeze, and vice versa. The reasons for these differences areunclear. Using unsupervised model-based cluster analysis, we identified latent clusters within aprospective birth cohort with deep immunological and respiratory phenotyping. We characterisedeach cluster in terms of immunological profile and disease risk, and replicated our results inexternal cohorts from the UK and USA. We discovered three distinct trajectories, one of which is ahigh-risk ‘atopic’ cluster with increased propensity for allergic diseases throughout childhood.Atopy contributes varyingly to later wheeze depending on cluster membership. Our findingsdemonstrate the utility of unsupervised analysis in elucidating heterogeneity in asthmapathogenesis and provide a foundation for improving management and prevention of childhoodasthma.